Macroinvertebrate trophic groups in an andean wetland of colombia (2013)
In the wetland Jaboque (Bogotá, Colombia) the physical and chemical properties of the water and the food dietary guilds of the aquatic macroinvertebrate community were analyzed from April 2009 to January 2010. The wetland waters had a slightly acid character with high values of nitrate, ammonia and orthophosphate, so this ecosystem is classified as eutrophic to hypereutrophic.In the aquatic macroinvertebrate community six food groups were recorded; they were conformed by 27 families, 26 confirmed genera and nine to be confirmed, with a total of 6,403 individuals collected in 28 samples of macrophytes. The highest abundances corresponded to detritivores (43.5 %), collector-scrapers (31.5 %), and collector-shredders (14.1 %), which were more abundantin the months of low rainfall. Stomach contents of some of the organisms showed that most of these individuals consumed more than one food type and high amounts of organic matter. Detrended correspondence analysis (DCA) showed a spatial (stations) and temporal (climatic seasons) organization, in which trophic guilds are grouped according to their niche requirements, environmental fluctuations or anthropogenic factors. Variations in dietary groups reflected changes in the macroinvertebrate community from a functional perspective and indicated that the wetland is very disturbed by urban activities.GRUPOS TRÓFICOS DE MACROINVERTEBRADOS ACUÁTICOS EN UN HUMEDAL URBANO ANDINO DE COLOMBIAEn el humedal Jaboque (Bogotá, Colombia) se analizaron las condiciones físicas y químicas del agua y se estudió la comunidad de macroinvertebrados acuáticos por grupos dietarios entre abril de 2009 y enero de 2010. Las aguas del humedal presentaron un carácter ligeramente ácido con valores altos de nitratos, nitrógeno amoniacal y fósforo, por lo que este ecosistema se clasificacomo eutrófico a hipereutrófico. La comunidad de macroinvertebrados acuáticos registró seis grupos alimenticios, los cuales estuvieron formados por 27 familias, 26 géneros confirmados y nueve géneros aún por confirmar, con un total de 6403 individuosrecolectados en 28 muestras de macrófitas. La mayor abundancia correspondió a detritívoros (43,5 %), colectores-raspadores(31,5 %) y colectores-fragmentadores (14,1 %), los cuales fueron más abundantes en los meses de menor precipitación. Los contenidos estomacales de algunos de los organismos evidenciaron que la mayoría de estos individuos consumieron más de un tipode alimento, además de altas cantidades de materia orgánica. El análisis de correspondencia linealizado (ACL) mostró una organización espacial (estaciones) y temporal (épocas climáticas) en la que los gremios tróficos se agrupan de acuerdo a sus requerimientos de nicho, fluctuaciones ambientales o factores de intervención humana. Las variaciones en los grupos dietarios reflejaron cambios en la comunidad de macroinvertebrados desde una perspectiva funcional e indicaron que el humedal es un sistema muy alterado por las actividades urbanas.